Absorbing aerosol influence on temperature maxima: An observation based study over India. (15th February 2020) - Dave, P.; Bhushan, M.; Venkataraman, C.
Abstract: Increasing trends in summer-time temperature maxima (Tmax) over India, show consequent increases in the intensity and frequency of heatwave events in recent years. Heat waves have been largely attributed to large-scale meteorological blocking, characterized by subsidence, clear skies and low soil moisture, in observational studies, or greenhouse gas enhancements in model studies. While radiative effects of absorbing aerosols are acknowledged, the association of absorbing aerosols with temperature maxima has not been investigated comprehensively. In the current study, statistical tools (such as correlation and Granger causality) were applied to long term (1979–2013) satellite and ground based observations to evaluate influence of absorbing aerosols on Tmax in north-west India (Tmax-NW). Regional absorbing aerosol index (AAI) in the north-west (AAI-NW) and central-India (AAI-CI) showed co-variability with Tmax-NW, implying connections to both local and non-local absorbing aerosols. The effects persisted on seasonal and heatwave event scales, becoming stronger on heatwave days with presence of enhanced AAI loadings. Causal effects of AAI-NW and AAI-CI were identified on Tmax-NW with a lag of 1–11 days, across multiple years, thereby establishing the influence of absorbing aerosols on heatwave events. The absence of confounding effects of surface pressure on these links suggests that, even during heat wave events linked to atmospheric blocking, absorbing aerosols can further enhance temperature maxima and related heatwave intensity. Highlights: Temperature maxima in northwest India correlate with absorbing aerosol abundance. Absorbing aerosols enhance local and non-local temperature maxima. The effect, lasting 1–11 days, exacerbates Tmax-2m during heatwave conditions.